2018
DOI: 10.1074/jbc.ra118.004442
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cholesterol biosynthesis overcomes enzalutamide resistance in castration-resistant prostate cancer (CRPC)

Abstract: Enzalutamide, a nonsteroidal second-generation antiandrogen, has been recently approved for the management of castration-resistant prostate cancer (CRPC). Although patients can benefit from enzalutamide at the beginning of this therapy, acquired enzalutamide resistance usually occurs within a short period. This motivated us to investigate the mechanism involved and possible approaches for overcoming enzalutamide resistance in CRPC. In the present study, we found that 3-hydroxy-3-methyl-glutaryl-CoA reductase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 31 publications
(29 reference statements)
2
72
0
Order By: Relevance
“…HMGCR inhibition by simvastatin further suppresses androgen signalling by lowering androgen-receptor levels via repression of signalling by mammalian target of rapamycin. A combination therapy of enzalutamide and simvastatin has been shown to have a significant synergistic effect on tumour suppression 123 .…”
Section: Enhancement Of Cd8 T Cell Function and Inhibition Of The Regmentioning
confidence: 99%
“…HMGCR inhibition by simvastatin further suppresses androgen signalling by lowering androgen-receptor levels via repression of signalling by mammalian target of rapamycin. A combination therapy of enzalutamide and simvastatin has been shown to have a significant synergistic effect on tumour suppression 123 .…”
Section: Enhancement Of Cd8 T Cell Function and Inhibition Of The Regmentioning
confidence: 99%
“…They showed that the combined treatment between simvastatin and enzalutamide sensitizes resistant cells in vitro. Moreover, tests in vivo in xenografts mice demonstrate a decrease in tumor cell proliferation (122).…”
Section: Targeting Lipid Metabolismmentioning
confidence: 99%
“…Nevertheless, how c-Myc is overexpressed in advanced PCa is not well studied. Our previous publications showed the contribution of β-catenin and PI3K/AKT/mTOR to ADT resistance (20,35). Considering that these two pathways are known to elevate c-Myc (36,37), and EphB4 acts upstream of β-catenin and PI3K/AKT/mTOR (7-9), it is reasonable to extrapolate that EphB4 and c-Myc work as the pivot to control the expression of AR through multiple signaling pathways in enzalutamide-resistant CRPC.…”
Section: Discussionmentioning
confidence: 98%